“Communicate Through the Roof”: A Case Study Analysis of the Communicative Rules and Resources of an Effective Global Virtual Team. - Scott, MurielE. (Communication Quarterly, 2013)
Challenges to effective collaboration are magnified when work teams are composed of geographically distributed members. Team members separated by time, distance, and culture often struggle with issues of trust, conflict, and potentially divisive subgroups. With global virtual teams becoming increasingly common in organizations, it is important to understand how to minimize such interactional difficulties. This study examines rules and resources that members of a corporate global team draw on to structure their interactions. In this case study, team members draw on highly ritualized actions prescribed by their software development process and their enacted values to mitigate their communication challenges.